Debating Glyphosate: A Macro Perspective on the Role of Strategic Communication in Forming and Monitoring A Global Issue Arena Using Inductive Topic Modelling. Issue 4 (7th August 2020) - Lock, Irina
ABSTRACT: Stakeholders debate issues of public interest in global online issue arenas, but political decision makers decide on these macro issues at national and supranational levels. A better understanding of the role of organizations in forming and monitoring such issue debates is necessary, given the influence of public affairs activities and media debates on politicians' and public opinion. However, such a macro perspective is largely missing. This study analyzes the debate around the use of the pesticide glyphosate when the European Union decided on a license renewal in 2017. To uncover emerging salient topics and their relations with organizations, the online global coverage of the issue from the GDELT database ( N = 1677) was analyzed using inductive automated content analysis (LDA topic modeling). Only three topics were salient in the arena, most prominently the carcinogenicity of glyphosate, thereby sidelining other relevant aspects. Furthermore, online issue arenas reach globally and are converged communicative spaces where a variety of media participate. Thus, the article develops and tests a typology of online news media for issue arena research. Advancing theory on organizations' roles and strategies in these online issue arenas, a new classification of actors based on their visibility and communication strategy is proposed.